1980
DOI: 10.1159/000115127
|View full text |Cite
|
Sign up to set email alerts
|

<i>L</i>-Dopa and the Secretion of Sebum in Parkinsonian Patients

Abstract: Sebum secretion was studied in 14 parkinsonian patients before and after 3 months of treatment with L-dopa. An abnormality of sebum secretion was shown to exist in parkinsonism. In 7 patients, successfully treated with L-dopa, sebum secretion diminished and its pattern improved. In all patients, in whom L-dopa treatment did not result in noticeable clinical changes, there was no significant modification in sebum secretion. No change was observed in the secretion of sebum of 5 normal control subjects, who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
1
5
0
1
Order By: Relevance
“…Bass et al (9) found weak positive correlation of sebum secretion with hypokinesia and rigidity, but not with tremor. Streifler et al (12) found no significant correlation between sebum secretion and clinical disability.…”
Section: Discussionmentioning
confidence: 96%
“…Bass et al (9) found weak positive correlation of sebum secretion with hypokinesia and rigidity, but not with tremor. Streifler et al (12) found no significant correlation between sebum secretion and clinical disability.…”
Section: Discussionmentioning
confidence: 96%
“…There are controversies concerning L-dopa effects on sebum excretion of Parkinsonian patients: some studies have reported a reducing effect (Agache and Blanc, 1982;Sparavigna et al, 1993) supporting the idea that seborrhea is accompanied by the blockade of a permanent inhibiting factor on sebum secretion, usually under brain dopamine control (Streifler et al, 1980;Harville and Appenzeller, 1978). Other authors have not yet found any effects (Plewig and Kligman, 1978), and many variations in the individual responses to L-dopa have been described.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the '70s, the first parkinsonian patient treated with L-dopa showed a reduction of seborrhea (Shuster and Thody, 1974;Streifler et al, 1980) suggesting that the disease was accompanied by the blockade of a permanent inhibiting factor on SER, usually under central dopaminergic control. In subsequent years a small number of studies concerning seborrhea have been published, the results of which are difficult to compare, due to the different methods used and the small number of subjects examined (Agache and Blanc, 1982;Villares and Carlini, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Confirmam-se portanto, as observações de Streifler et al 27 e Agnoli et al 2 . Em relação ao sexo feminino a terapêutica não foi efetiva, provavelmente, em decorrência do pequeno número de avaliados.…”
Section: Comentáriosunclassified